(untitled) (Fort Worth, 2000)
This book provides a rigorous background in the chemical principles and introduces a wide range of techniques of analytical chemistry
Nghiên cứu phức chất bằng trắc quang,TT. Hóa phân tích 1,TT. Hóa phân tích 2,Hóa phân tích 1,Hóa phân tích 2,Anh văn chuyên môn - Hóa học,Hóa phân tích đại cương,TT. Hóa phân tích đại cương
Keywords: Chemistry, Analytic,Hóa học phân tích; Quantitative,Định lượng